Reassessment of Rebleeding Risk of Forrest IB (Oozing) Peptic Ulcer Bleeding in a Large International Randomized Trial. (March 2017) - Jensen, Dennis M; Eklund, Stefan; Persson, Tore; Ahlbom, Henrik; Stuart, Robert; Barkun, Alan N; Kuipers, Ernest J; Mössner, Joachim; Lau, James Y; Sung, Joseph J; Kilhamn, Jan; Lind, Tore
Abstract : OBJECTIVES: Our aims were to assess risks of early rebleeding after successful endoscopic hemostasis for Forrest oozing (FIB) peptic ulcer bleeding (PUBs) compared with other stigmata of recent hemorrhage (SRH). METHODS: These were post hoc multivariable analyses of a large, international, double‐blind study (NCT00251979) of patients randomized to high‐dose intravenous (IV) esomeprazole (PPI) or placebo for 72 h. Rebleeding rates of patients with PUB SRH treated with either PPI or placebo after successful endoscopic hemostasis were also compared. RESULTS: For patients treated with placebo for 72 h after successful endoscopic hemostasis, rebleed rates by SRH were spurting arterial bleeding (FIA) 22.5%, adherent clot (FIIB) 17.6%, non‐bleeding visible vessel (FIIA) 11.3%, and oozing bleeding (FIB) 4.9%. Compared with FIB patients, FIA, FIIB, and FIIA had significantly greater risks of rebleeding with odds ratios (95% CI's) from 2.61 (1.05, 6.52) for FIIA to 6.66 (2.19, 20.26) for FIA. After hemostasis, PUB rebleeding rates for FIB patients at 72 h were similar with esomeprazole (5.4%) and placebo (4.9%), whereas rebleed rates for all other major SRH (FIA, FIIA, FIIB) were lower for PPI than placebo, but the treatment by SRH interaction test was not statistically significant. CONCLUSIONS: After successful endoscopic hemostasis, FIB patients had very low PUB rebleeding rates irrespective of PPI or placebo treatment. This implies that after successful endoscopic hemostasis the prognostic classification of FIB ulcers as a high‐risk SRH and the recommendation to treat these with high‐dose IV PPI's should be re‐evaluated.